The aggregation effect of organic matter on bauxite residue particles and its improvement mechanism - Dong, Mengyang; Wang, Guizhen; Gul Wazir, Zafran; Liu, Jing; Hou, Guoqin; Gao, Xinyu; Chao, Liang; Rong, Fangxu; Xu, Yuzhi; Li, Mingyue; Liu, Kai; Liu, Aiju; et al. (Frontiers in Environmental Science, 2023)
Introduction: Understanding organic amendment and the agglomeration of bauxite residue particles is vital to soil amelioration of bauxite residues. In this study, a pot culture experiment was conducted to illustrate the aggregation of organic amendment on bauxite residues particles and its improvement mechanism. The single organic amendment and its combination with soil inoculum were conducted to explore the aggregation effect of organic matter on bauxite residue particles, and its correlations with microbial rehabilitation. Methods: The dry- and wet-sieving method were used to obtain different sizes of aggregates. The concentrations of soil organic carbon and iron and aluminum (Fe/Al) oxides in the forms extractable by DCB (Fed/Ald) and oxalate (Fe0/Al0) were measured. Microbial rehabilitation after 180 days incubation was determined with the methods of Biolog Ecoplate™ and the high-throughput sequencing. Results and Discussion: The results showed that over 180 days incubation, the alkalinity of bauxite residues was significantly decreased with the organic amendment based on the value of pH, EC and ESP (down to 9.26, 0.61 m/cm and 55.5%, respectively, in HS3). Secondly, organic amendment significantly promoted microbial community establishment and ecological function recovery. Moreover, the MWD value of aggregates also increased to 0.73 mm from the initial 0.32 mm, companied with the increase of the Fe/Al oxidizes. The further Pearson relationship analysis and the characterization of EPMA and SEM indicated that the organic matter and Fe/Al oxides played important roles in cementing fine bauxite residues particles and increasing aggregates stability, while this aggregation process was accelerated by the establishment of microbial ecology in bauxite residues. Therefore, organic amendment was more implication in soil amelioration of bauxite residues other than the directive modifications on alkalinity.